Correlation of Ventricular Arrhythmogenesis with Neuronal Remodeling of Cardiac Postganglionic Parasympathetic Neurons in the Late Stage of Heart Failure after Myocardial Infarction - Zhang, Dongze; Tu, Huiyin; Wang, Chaojun; Cao, Liang; Muelleman, Robert L.; Wadman, Michael C.; Li, Yu-Long (Frontiers in Neuroscience, 2017)
Introduction: Ventricular arrhythmia is a major cause of sudden cardiac death in patients with chronic heart failure (CHF). Our recent study demonstrates that N-type Ca2+ currents in intracardiac ganglionic neurons are reduced in the late stage of CHF rats. Rat intracardiac ganglia are divided into the atrioventricular ganglion (AVG) and sinoatrial ganglion. Only AVG nerve terminals innervate the ventricular myocardium. In this study, we tested the correlation of electrical remodeling in AVG neurons with ventricular arrhythmogenesis in CHF rats. Methods and results: CHF was induced in male Sprague-Dawley rats by surgical ligation of the left coronary artery. The data from 24-hour continuous radiotelemetry ECG recording in conscious rats showed that ventricular tachycardia/fibrillation (VT/VF) occurred in 3-week and 14-week CHF rats but not 8-week CHF rats. Additionally, as an index for vagal control of ventricular function, changes of left ventricular systolic pressure (LVSP) and the maximum rate of left ventricular pressure rise (LV dP/dtmax) in response to vagal efferent nerve stimulation were blunted in 14-week CHF rats but not 3-week or 8-week CHF rats. Results from whole-cell patch clamp recording demonstrated that N-type Ca2+ currents in AVG neurons began to decrease in 8-week CHF rats, and that there was also a significant decrease in 14-week CHF rats. Correlation analysis revealed that N-type Ca2+ currents in AVG neurons negatively correlated with the cumulative duration of VT/VF in 14-week CHF rats, whereas there was no correlation between N-type Ca2+ currents in AVG neurons and the cumulative duration of VT/VF in 3-week CHF. Conclusion: Malignant ventricular arrhythmias mainly occur in the early and late stages of CHF. Electrical remodeling of AVG neurons highly correlates with the occurrence of ventricular arrhythmias in the late stage of CHF.